Current State of Normative and Legal Regulation of the Rehabilitation Institution in Criminal Proceedings of Ukraine - H. I. Hlobenko (Bulletin of Kharkiv National University of Internal Affairs)
The authir has carried out theoretical study of the current state of regulation of the rehabilitation institution in criminal proceedings of Ukraine, the immediate task of which is to protect human and civil rights and freedoms within relations between the state and an individual. Numerous appeals to the ECHR by citizens of Ukraine, who have been illegally or unjustifiably prosecuted, as well as the existence of decisions in their favor indicate on the shortcomings of this institution.